Manajemen Sumber Daya Manusia Dalam Gereja - Taturu, Ambarwaty P.I.P (Peneliti.net, 2024)
This research aims to examine the concept of human resource management (HRM) in the context of the church. HR is an important asset that must be managed properly to support the growth and progress of the church. This research uses qualitative research methodology and descriptive approach. Data was collected through desk research using literature relevant to the research topic. The discussion of this research includes the concept of management, definitions from several experts, and elements related to management. Management is defined as the art of organizing human resources and other resources to achieve organizational goals. In the context of the church, church members are church human resources who have an important role in influencing the quality of church institutions. Therefore, the church needs to maximize its church HR to achieve church goals. This research concludes that church HR management is an important aspect of church management. Church HR management involves planning, organizing, leading, and controlling. Although the concept of management has different definitions, it still has the same goal of achieving organizational goals effectively and efficiently.